Ameliorative Effect of Ethanolic Extract of Cichorium intybus on Cisplatin - Induced Nephrotoxicity in Rats: Cichorium intybus as Antioxidant for Nephrotoxicity (Biological Sciences - PJSIR, 2009)
In the study of the possible ameliorative effect of the Cichorium intybus vs. cisplatin-induced nephrotoxicity, no sign of toxicity was observed in rats on administration of ethanolic extract of C. intybus (500 mg/kg) with cisplatin (3 mg/kg). Oral administration of C. intybus extract reduced cisplatin-induced nephrotoxicity and also prevented elevated plasma creatinine, urea and nitrate, plasma and tissue MDA levels and restored antioxidant enzymes.